Project-Based Learning and Translation Shifts in the Descriptive Texts: A Qualitative Study among Indonesian English Education Students - Sanggam Siahaan; Basar Lolo Siahaan; Siska Anggita Situmeang (JETAL: Journal of English Teaching & Applied Linguistic, 2026)
This study was to know the use of shift types in the translation of descriptive texts found in the online English Textbook published for grade 10th students in Indonesia. It engaged 39 English Education Study Program students of the University of HKBP Nommensen Pematangsiantar, Indonesia, to use Indonesian linguistic codes to replace English linguistic codes in the translation of descriptive texts. It applied a qualitative method design and randomly selected 4 projects out of 39 student-translation project portfolios. Three concurrent activities: data collection/reduction, data display, and conclusion draw/verification were used to analyze the shift types. The results were dominantly structure shifts, 83.3%, and unit shifts, 16.7%, in project 1; structure shifts, 100%, in project 2; unit shifts, 57.14% and class shifts, 21.42%, in project 3; and level shifts, 40.74%, and structure shifts, 44.44% in project 4. The students tended to used structure shifts and class shifts to keep translation fidelity, accuracy, adequacy, fluency, and coherence from English descriptive texts into Indonesian through Project-Based Learning. It needs to engage more subjects and data to shed pedagogical light to improve students’ ability in the translation of English narrative texts into Indonesian.